An Examination of the Effects of Electronic Word of Mouth on Consumers’ Purchase Decision: Through the Lens of Experience Good and Search Good - Zhao, Zichen (2013)
The prevailing of the Internet facilitates consumers to share information, opinions and experiences of products and services online. This new form of word of mouth communication is called electronic word of mouth (WOM). Nowadays, electronic word of mouth plays an important role in the consumers’ information search during the decision making process. A large number of managerial and academic attentions have been drawn to the effects of electronic WOM on consumer’s purchase decision. Factors which could affect the effectiveness of electronic WOM are also largely examined by a lot of studies. However, few of them stressed the effect of electronic WOM on consumers’ purchase decision from the perspective of different product types. This study investigates the effect of electronic WOM on consumers’ purchase decision in the lens of product types which are experience good and search good. By conducting the study using quantitative research method, the result shows that for different product types the same factor might have different degrees of impacts on the effectiveness of electronic WOM. Meanwhile, the result also shows that consumers have different electronic WOM search behaviours associated with different product types. Based on the empirical result, this study could provide both academic and managerial implications.